2013
DOI: 10.1111/cen.12355
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic ultrasound findings in prepubertal girls with precocious adrenarche born appropriate for gestational age

Abstract: Appropriate for gestational age-born PA girls have greater UL measurements than AGA-born BMI-matched peers. In AGA-born girls with PA, decreasing insulin sensitivity is strongly and independently associated with an increase in MOV. Longitudinal follow-up of our cohort after menarche will allow us to establish how many AGA-born girls with PA will ultimately develop PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(92 reference statements)
1
3
0
Order By: Relevance
“…Our results align with this group in that 65% our PA cohort had above lab reference testosterone levels. Uçar et al [28] also demonstrated higher testosterone levels (45.1 pmol/L vs. 31.2 pmol/L, P =0.001) in Turkish girls with PA (n=56) when compared to control girls (n=33) using an RIA assay similar to ours. On the other hand, Paterson et al [27] did not find elevated testosterone in Scottish girls when compared to normal reference range using a chemiluminescent assay (mean+SD [range]).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results align with this group in that 65% our PA cohort had above lab reference testosterone levels. Uçar et al [28] also demonstrated higher testosterone levels (45.1 pmol/L vs. 31.2 pmol/L, P =0.001) in Turkish girls with PA (n=56) when compared to control girls (n=33) using an RIA assay similar to ours. On the other hand, Paterson et al [27] did not find elevated testosterone in Scottish girls when compared to normal reference range using a chemiluminescent assay (mean+SD [range]).…”
Section: Discussionsupporting
confidence: 84%
“…Since there are many studies that report a high incidence of PCOS in girls with PA, this study attempted to verify if the AMH level is higher in PA girls. One study with Scottish girls reports that the AMH level is higher in PA girls, and 3 studies including this study (Uçar, Utriainen, and this study) report that there is no difference in AML level between the 2 groups [27,28,39]. Two of the 3 studies reporting no difference in AMH levels (Ucar and this study) showed no difference in BMI between the 2 groups, but Utriainen’s study found a significant difference in the BMI between the 2 groups in and compared the AMH level while controlling the BMI.…”
Section: Discussionmentioning
confidence: 67%
“…In another study from our group, Ucar et al 28 reported that AGA born girls with PA had greater uterine length than their BMI‐matched healthy peers. Although mean ovarian volumes were not significantly different between the groups in that study, decreasing insulin sensitivity was strongly associated with an increase in mean ovarian volume 28 .…”
Section: Discussionmentioning
confidence: 75%
“…In another study from our group, Ucar et al 28 reported that AGA born girls with PA had greater uterine length than their BMI‐matched healthy peers. Although mean ovarian volumes were not significantly different between the groups in that study, decreasing insulin sensitivity was strongly associated with an increase in mean ovarian volume 28 . We could not find any significant association between metabolic parameters and ovarian volumes in this study but, we found a positive association between insulin levels and endometrial thickness.…”
Section: Discussionmentioning
confidence: 75%